Evaluation of an integrated methane autothermal reforming and high-temperature proton exchange membrane fuel cell system - Authayanun, Suthida; Saebea, Dang; Patcharavorachot, Yaneeporn; Arpornwichanop, Amornchai (My University, 2015)
The aim of this study was to investigate the performance and efficiency of an integrated autothermal reforming and HT-PEMFC (high-temperature proton exchange membrane fuel cell) system fueled by methane. Effect of the inclusion of a CO (carbon monoxide) removal process on the integrated HT-PEMFC system was considered. An increase in the S/C (steam-to-carbon) ratio and the reformer temperature can enhance the hydrogen fraction while the CO formation reduces with increasing S/C ratio. The fuel processor efficiency of the methane autothermal reformer with a WGS (water gas shift reactor) reactor, as the CO removal process, is higher than that without a WGS reactor. A higher fuel processor efficiency can be obtained when the feed of the autothermal reformer is preheated to the reformer temperature. Regarding the cell performance, the reformate gas from the methane reformer operated at Tin=TR and with a high S/C ratio is suitable for the HT-PEMFC system without a WGS reactor. When considering the HT-PEMFC system with a WGS reactor, the CO poisoning has less significant impact on the cell performance and the system can be operated over a broader range to minimize the required total active area. A WGS reactor is necessary for the methane autothermal reforming and HT-PEMFC integrated system with regard to the system efficiency.
Keywords: Autothermal reforming; HT-PEMFC (high-temperature proton exchange membrane fuel cell); Methane; Performance analysis